Національному гербарію України — 90 років - Шиян, Н.М.; Дудка, І.О.; Кондратюк, С.Я.; Царенко, П.М.; Вірченко, В.М.; Безусько, Л.Г. (Український ботанічний журнал, 2012)
В 2011 году Национальный гербарий Украины (KW) отмечает 90-летие со дня своего основания. Сегодня KW насчитывает 2 040 000 единиц хранения и состоит из нескольких подразделений: гербария сосудистых растений (1 839 583 образцов), микологического (86 520 образцов), лихенологического (63 000 образцов), бриологического (37 400 образцов) гербариев, альготеки (27 810 образцов) и палинотеки (1 109 образцов). В статье рассмотрены основные достижения KW за последнее десятилетие. In 2011 the National Herbarium of Ukraine (KW) celebrates 90 years since it was founded. At present the KW Herbarium contains 2.04 million specimens. It consists of several divisions, including the Herbarium of Vascular Plants (1 839 583 specimens), the Mycological Herbarium (86 520 specimens), the Herbarium of Lichens (63 000 specimens), the Bryological Herbarium (37 400 specimens), the Algotheca (27 810 specimens), and the Palynotheca (1 109 specimens). In the article, the last de cade’s achievements of the KW Herbarium are considered.